Food Severed At Manjalang Mintuo Ceremony At Nagari Lubuk Alai - Anjelya, Fitri; Syarif, Wirnelis (Jurnal Pendidikan Tata Boga dan Teknologi, 2022)
This study to describe the types of food served and the recipes of the food served at the manjalang mintuo event in Nagari Lubuak Alai. This study used qualitative research methods. The research was carried out in Nagari Lubuak Alai from July 2 to August 7, 2021. The data sources were obtained from bundo kanduang and people who know about the manjalang mintuo event in Nagari Lubuak Alai. Research data in the form of observations, interviews and documentation to informants. The results of this study indicate the types of food served at the manjalang mintuo event in Nagari Lubuak Alai, namely: staple food consisting of: rice, side dishes consisting of chicken curry, fish food and beef rendang, chili sauce served namely: red chili and chili sauce. green chili sauce, vegetables served in the form of boiled chickpeas and pickles and the cakes served are: sponge cake, and agar-agar. A recipe is a guide in which there is the name of the meal, the results of the dish, the ingredients and the amount to be used, the tools needed and how to process the food in order to facilitate the processing.